Efficacy of endoscopic treatment for chronic subdural hematoma surgery. (October 2021) - Amano, Toshiyuki; Miyamatsu, Yuichiro; Otsuji, Ryosuke; Nakamizo, Akira
Highlights: Endoscopic treatment takes longer, but is useful and safe, in CSDH surgery. Endoscopic treatment is useful for complicated CSDH with a clot and/or a septum. Endoscopic treatment in CSDH surgery reduces the incidence of CSDH recurrence. Endoscopic treatment is an independent factor for reducing postoperative rebleeding. Complicated CSDH may be an optimal indication for endoscopic treatment. Abstract: Endoscopic treatment is a potential therapeutic addition to chronic subdural hematoma (CSDH) surgery. However, the effect of endoscopic treatment remains controversial. Herein, we examined the optimal indication for endoscopic treatment in CSDH surgery. We retrospectively analyzed 380 consecutive patients with CSDH who underwent single burr-hole craniostomy. We defined postoperative rebleeding as radiological re-accumulation or increased computed tomography value of the hematoma. Reoperation was performed following further hematoma accumulation and/or neurological deterioration. Complicated CSDH was radiologically defined as a hematoma with a clot and/or fibrous septum. There were no differences in baseline characteristics or postoperative mortality and morbidity between the endoscope (97 patients) and control (283 patients) groups. The incidence of postoperative rebleeding (9.3% vs 25.1%, respectively; P = 0.001) and reoperation (0% vs 9.2%, respectively; P = 0.004) were significantly lower in the endoscope group versus controls. Multivariate analysis showed that males (odds ratio 2.14, 95% confidence interval 1.19–3.81; P = 0.012) and endoscopy (odds ratio 0.29, 95% confidence interval 0.13–0.59; P = 0.001) were independently associated with postoperative rebleeding. When CSDHs were divided into two types based on hematoma component, 175 patients exhibited complicated CSDH. There was a significant reduction in postoperative rebleeding (6.5% vs 23.0%, respectively; P = 0.010) and reoperation (0% vs 9.7%, respectively; P = 0.027) in complicated CSDH patients. Endoscopic treatment in CSDH surgery does not increase the risk of surgical complications. Complicated CSDH with a clot and/or septum may be an optimal indication for endoscopic treatment in CSDH surgery to reduce postoperative recurrence.